A comparison of the endotoxin biosynthesis and protein oxidation pathways in the biogenesis of the outer membrane of Escherichia coli and Neisseria meningitidis - Piek, Susannah; Kahler, Charlene M. (Frontiers in Cellular and Infection Microbiology, 2012)
The Gram-negative bacterial cell envelope consists of an inner membrane (IM) that surrounds the cytoplasm, and an asymmetrical outer-membrane (OM) that forms a protective barrier to the external environment. The OM consists of lipopolysaccahride (LPS), phospholipids, outer membrane proteins (OMPs) and lipoproteins. Oxidative protein folding mediated by periplasmic oxidoreductases is required for the correct biogenesis of the protein components, mainly constituents of virulence determinants such as pili, flagella and toxins, of the Gram-negative OM. Recently, periplasmic oxidoreductases have been implicated in LPS biogenesis of Escherichia coli and Neisseria meningitidis. Differences in OM biogenesis, in particular the transport pathways for endotoxin to the OM, the composition and role of the protein oxidation and isomerisation pathways and the regulatory networks that control them have been found in these two Gram-negative species suggesting that although form and function of the OM is conserved, these conserved pathways have been modified to suit the lifestyle of each organism.